2023
DOI: 10.1186/s12940-022-00955-8
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood infrastructure-related risk factors and non-communicable diseases: a systematic meta-review

Abstract: Background With rapid urbanization, the urban environment, especially the neighborhood environment, has received increasing global attention. However, a comprehensive overview of the association between neighborhood risk factors and human health remains unclear due to the large number of neighborhood risk factor–human health outcome pairs. Method On the basis of a whole year of panel discussions, we first obtained a list of 5 neighborhood domains, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…26 In contrast, another review found that associations of access to facilities for physical and leisure activities were null or inconsistent for coronary heart disease, stroke, and type 2 diabetes. 28 Systematic reviews have found null associations of the food environment with CVD-related outcomes overall, but some evidence linking the fast-food environment to higher weight and CVD. [27][28][29] Living in neighborhoods with higher levels of air pollution has been linked to poorer endothelial function and adverse cardiovascular outcomes, including hospitalization and mortality.…”
Section: Neighborhood Physical and Social Environments And Cvhmentioning
confidence: 99%
See 4 more Smart Citations
“…26 In contrast, another review found that associations of access to facilities for physical and leisure activities were null or inconsistent for coronary heart disease, stroke, and type 2 diabetes. 28 Systematic reviews have found null associations of the food environment with CVD-related outcomes overall, but some evidence linking the fast-food environment to higher weight and CVD. [27][28][29] Living in neighborhoods with higher levels of air pollution has been linked to poorer endothelial function and adverse cardiovascular outcomes, including hospitalization and mortality.…”
Section: Neighborhood Physical and Social Environments And Cvhmentioning
confidence: 99%
“…26 In contrast, another review found that associations of access to facilities for physical and leisure activities were null or inconsistent for coronary heart disease, stroke, and type 2 diabetes. 28 Systematic reviews have found null associations of the food environment with CVD-related outcomes overall, but some evidence linking the fast-food environment to higher weight and CVD. 27–29…”
Section: Observational Studies Examining the Contribution Of Neighbor...mentioning
confidence: 99%
See 3 more Smart Citations